2016
DOI: 10.1097/ijg.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on Outcome Measures for Glaucoma Effectiveness Trials: Results From a Delphi and Nominal Group Technique Approaches

Abstract: Consensus was reached among glaucoma experts on how best to measure IOP, VF, and anatomic outcomes in glaucoma randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 23 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…A systematic review by Ismail and associates showed that a large variability exists in outcomes selected in glaucoma Cochrane Reviews and Protocols, with IOP being the most commonly used outcome measure; in addition, inconsistency was noted among those reviews and protocols. 2123 Our main outcome measures were trabeculectomy failure and mean IOP at 24 and 12 months postoperatively. However, glaucoma is a chronic disease and long-term follow-up is needed to assess surgical success.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Ismail and associates showed that a large variability exists in outcomes selected in glaucoma Cochrane Reviews and Protocols, with IOP being the most commonly used outcome measure; in addition, inconsistency was noted among those reviews and protocols. 2123 Our main outcome measures were trabeculectomy failure and mean IOP at 24 and 12 months postoperatively. However, glaucoma is a chronic disease and long-term follow-up is needed to assess surgical success.…”
Section: Discussionmentioning
confidence: 99%
“…32 For cataract, the available core outcome set includes 4 outcomes, 33 of which 3 (visual acuity, ocular adverse events, and vision-related quality of life) are common to the 7 most frequent outcomes in our sample of trials and reviews. Similarly, for glaucoma, the available core outcome set includes 4 outcomes, 35 of which 3 (intraocular pressure, visual field, and ocular adverse events) are common to the 7 most frequent outcomes in our sample of trials and reviews. In addition to published core outcome sets, core outcome sets are being developed for AMD, uveitis, DR, visual impairment after stroke, amblyopia, strabismus, and ocular motility.…”
Section: Discussionmentioning
confidence: 99%
“…Because a ‘Summary of findings’ table was not part of the original Cochrane protocol, we chose the outcomes presented in the table post hoc. We based our selection on core outcomes for glaucoma research that have been proposed in the literature (Ismail 2016). The main outcomes for this review include:…”
Section: Methodsmentioning
confidence: 99%